Work Environment and Career Development Opportunities on Salesman Performance: The Mediating Role of Job Satisfaction in Pasukan Garuda PT HM Sampoerna - Anwar, Maya; Sutrisno, Timotius FCW (SAFE-Network, 2025)
This study investigates the influence of work environment and career development opportunities on salesman performance with job satisfaction as a mediating variable, focusing on the Pasukan Garuda unit of PT HM Sampoerna in Pamekasan–Madura. A quantitative approach with descriptive and explanatory methods was employed, using a census sample of 66 salesmen. Data were collected through a structured questionnaire consisting of 19 indicators measured on a five-point Likert scale and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0. The measurement model demonstrated validity and reliability, with factor loadings above 0.70, Cronbach’s Alpha and Composite Reliability exceeding 0.70, and AVE values greater than 0.50. The structural model showed that work environment had both direct and indirect positive effects on performance, while job satisfaction emerged as the strongest predictor and a significant mediator. Conversely, career development opportunities significantly affected job satisfaction but did not directly improve performance, and the mediating pathway was not statistically supported. The R² values indicated that predictors explained 35% of the variance in job satisfaction and 88.9% of the variance in performance. Overall, the study concludes that enhancing work environment and job satisfaction are the most effective strategies to strengthen sales force performance in competitive contexts.